Collagen cross-linking in recalcitrant corneal ulcers: A case series - Agrawal, Nisha; Singh, S K (Nepalese Journal of Ophthalmology, 2016)
Introduction: Corneal ulcer is a leading cause of blindness worldwide. Many of these patients don’t respond to conventional treatment with topical agents. Collagen cross-linking (CXL) has been suggested to avoid complications requiring emergency keratoplasty. Subjects and methods: Six eyes with presumed bacterial keratitis not responding to conventional treatment underwent CXL with ultraviolet A rays and transepithelial riboflavin. Patients with Descematocele and perforated ulcers were excluded. Preoperatively and postoperatively slit lamp examination of cornea and visual acuity recording was done. Postoperative outcome included subjective symptoms like relief in pain, photophobia, lacrimation and objective signs like improvement in epithelisation, corneal scarring with vascularisation. Results: Four of the six eyes healed completely with scarring at 2 months follow-up. One of the patients developed Descematocele on 12 days which perforated later. Other patient developed Descematocele on 20 days post CXL. Of the subjective symptoms, pain and epiphora improved in all the patients except one. Photophobia improved only a week after CXL in four out of six patients. Epithelial defect completely healed over time in four out of six cases. All the cases who responded to treatment developed superficial and deep vascularisation of the cornea. Decrease in corneal edema and scarring was noted in four out of the six cases. Conclusion: The collagen cross-linking has a beneficial role as an adjuvant to medical therapy in recalcitrant bacterial keratitis. It helps in relief of pain and healing of ulcer. Larger randomized control trails with longer follow-up are required to come to a definite conclusion. Nepal J Ophthalmol 2016; 8(15): 47-53